Anodic Oxidation of Catechol in Presence of Some Active Methylene Compounds - Bakhsh Raoof, Jahan; Ojani, Reza; Kiani, Abolfazl (Asian Journal of Chemistry, 2010)
The electrochemical generation of o-benzoquinone from catechol and its subsequent reaction with the some active methylene compounds such as diethyl malonate, ethyl acetoacetate and diethyl bromomalonate have been investigated using cyclic voltammetry. The results indicate that the o-benzoquinone derived form the anodic oxidation of catechol participates in Michael addition reaction with active methylene compounds as nucleophiles to form the corresponding adducts. The rate of Michael addition reaction showed dependence on applied active methylene compounds. While, the electrochemical behaviour of catechol in the presence of diethyl bromomalonate could be described by an ECE mechanism, in the presence of diethyl malonate and ethyl acetoacetate.